Unusual Laparoscopy Finding with Previous Laparotomy for Endometrioma: A Rare Case Report - Wahi, Meenu (Medknow Publications & Media Pvt Ltd, 2009)
An unmarried girl with severe dysmenorrhea had laparotomy for bilateral endometriomas, later treated with danazol and GnRHa Depo injection for more than three years. On laparoscopy she had a large, noncommunicating, functioning rudimentary horn with ipsilateral renal agenesis. Laparoscopic excision of the rudimentary horn gave major relief from the suspected endometrioma, which was not the cause of her severe pain.